Shopee Pay Free Shipping Promotion Moderation On Customer Satisfaction - Yusfita Dyah Fanani (Yayasan Gema Bina Nusantara, 2023)
The reason for this observation become to partly and concurrently decide the impact of service quality on customer satisfaction in Tangerang city, and to decide the variable of free shipping promotion as a moderator variable of service quality on customer satisfaction. Pattern length changed into determining the usage of a purposive sampling technique with a minimum of 96 respondents. The lowest population for this has an observed is her Shoppe customers in Tangerang city who take gain of free shipping on their Shopee purchases. This observation is an associative causal test. data collection equipment is inside the shape of digital surveys distributed thru Google forms. data analysis techniques the use of the JASP 0.16.4 software program. The service exceptional results had a massive advantageous effect on client satisfaction with a t-statistic of 6,610, and the free shipping marketing campaign payment promoting had a good sized impact on customer satisfaction with a t-statistic of 2,083 from the carrier high-quality survey and free delivery promotion impact. Make a big nice impact. The F-test result is 72,936, which has a big positive effect on customer satisfaction. A Sobel takes a look at the rating of 2.027 > 1.986 indicating that the free delivery advertising variable is a moderator of quality of service variables related to customer satisfaction. Based on the results with a coefficient of determination of 0.601, it suggests that distinct Shopee promotions on free shipping and provider quality can explain 60.1% of his Shopee customer satisfaction in Tangerang city.